Cutting-edge Innovations in Oleanolic Acid Formulation - Gohil, Dipti (Asian Journal of Pharmaceutics (AJP), 2025)
Oleanolic acid (OA), a naturally occurring pentacyclic triterpenoid, has garnered significant attention due to its broad spectrum of pharmacological activities. Despite its therapeutic potential, the clinical application of OA is limited by its poor water solubility and low bioavailability, which hinder effective systemic absorption and therapeutic efficacy. Advances in pharmaceutical formulation technologies have addressed these challenges, paving the way for enhanced delivery systems that improve OA solubility, stability, and bioavailability. Among the most promising strategies are nanoformulations, including lipid-based nanoparticles, polymer-based nanocarriers, and solid lipid nanoparticles (SLNs). Lipid-based systems such as liposomes and nanoemulsions not only protect OA from environmental degradation but also facilitate controlled release and improved skin permeability, making them suitable for topical delivery. Polymeric carriers and micelles offer targeted delivery and sustained drug release, while SLNs enhance drug loading and stability. Characterization techniques such as dynamic light scattering, zeta potential analysis, electron microscopy, and differential scanning calorimetry ensure formulation quality, stability, and performance. These advanced delivery systems significantly improve the pharmacokinetic profile and therapeutic potential of OA.